Quality of care and respect of human rights in mental health services in four West African countries: collaboration between the mental health leadership and advocacy programme and the World Health Organization QualityRights initiative. Issue 1 (25th January 2022) - Moro, Maria Francesca; Kola, Lola; Fadahunsi, Olawoye; Jah, Edward Munda; Kofie, Humphrey; Samba, Dawda; Thomas, Sametta; Drew, Natalie; Nwefoh, Emeka; Pathare, Soumitra; Eaton, Julian; Funk, Michelle; et al.
Abstract : Background: Although recent reports suggest that service users in West African psychiatric facilities are exposed to poor quality of care and human rights violations, evidence is lacking on the extent and profile of specific deficits in the services provided to persons with mental health conditions. Aims: To evaluate the quality of care and respect of human rights in psychiatric facilities in four West African countries, The Gambia, Ghana, Liberia and Sierra Leone, using the World Health Organization QualityRights Toolkit. Method: Trained research workers collected information through observation, review of records and interviews with service users, caregivers and staff. Independent panels of assessors used the information to assign scores to the criteria, standards and themes of the QualityRights Toolkit. Results: The study revealed significant gaps in these facilities. The rights to an adequate standard of living and to enjoyment of the highest attainable standard of health were poorly promoted. Adherence to the right to exercise legal capacity and the right to personal liberty and security was almost absent. Severe shortcomings in the promotion of the right to live independently and be included in the community were reported. Conclusions: Inadequate appreciation of service users' rights, lack of basic approaches to protect them and the non-promotion of rights-based services in these facilities are major problems that need to be addressed. Although it recognises the resource constraints and need for more human and financial resources, the study also identifies critical areas and challenges that require significant changes at the facility level.